Application of Travel Cost Method in Economic Valuation at Gumuk Kantong Muncar Banyuwangi Beach - Dwi Saputra, Nanda; Purwaningtyas, Ayu; Nur Jannah, Reni (Jurnal Manajemen Perhotelan dan Pariwisata, 2024)
Gumuk Kantong Beach is one of the beaches in Muncar sub-district, Banyuwangi Regency. This beach was previously known as a dirty beach which was then managed as a tourist attraction. The entrance ticket price has increased from year to year and in 2023 the entrance ticket price will increase to 100%, so the management gets complaints from visitors. The aim of this research is to identify the characteristics of visitors to Gumuk Kantong Beach, analyze the factors that influence the demand for visits to Gumuk Kantong Beach, estimate the economic value of Gumuk Kantong Beach using the Travel Cost Method approach and estimate the potential revenue for Gumuk Kantong Beach in 2024 based on entrance ticket prices. The research method used in this research uses quantitative research with the Travel Cost Method approach. The research method uses several tests, namely descriptive statistical tests, inferential statistical tests, and quantitative analysis. The number of samples used in this research was 45 respondents. The analysis method used is multiple linear regression. The hope of this research is the economic value of Gumuk Kantong beach, visit demand factors and also estimates of visit demand. The research method uses several tests, namely descriptive statistical tests, inferential statistical tests, and quantitative analysis. The number of samples used in this research was 45 respondents. The analytical method used is multiple linear regression with the Ordinary Least Square (OLS) method. The research results show that the factors that have a significant influence on visiting Gumuk Kantong Beach with an error rate of 5% are travel costs and age. The consumer surplus value of Gumuk Kantong Beach per visit per person is IDR. 7,518. The economic value of Gumuk Kantong Beach per year is IDR. 1,195,384,554. This value shows that visitors still have the desire to maintain the sustainability of Gumuk Kantong Beach as a tourist location in Banyuwangi, East Java.